When through deep waters - Dekker, Rachelle (Tyndale House Publishers, Inc., 2018)
Alicen McCaffrey is happy with her life in Santa Monica, Calif. Although she believes her husband may not be faithful, she finds joy in her five-year-old daughter, Jane. But when Jane dies in a tragic accident in the backyard pool, Alicen feels she has lost everything, including her will to live.